The Role of Discipline and Motivation towards Employee Job Satisfaction of Manufacture Company in Sidoarjo, Indonesia - M. Fahmi Kurniawan; As'at Rizal (Indonesian Journal of Law and Economics Review, 2019)
This study aims to determine the effect of incentives, work discipline, and motivation partially and simultaneously on job satisfaction of PT Sentra Bumi Nirwana employees. This research uses descriptive quantitative type. The research sample was 61 employees. The data source of this research is a secondary data source. Data collection techniques are done by interview / questionnaire and documentation. Data analysis techniques using the help of SPSS 20.0. the results of this study indicate that incentives have a significant positive effect directly on job satisfaction of PT Sentra Bumi Nirwana employees, discipline has a significant positive effect directly on job satisfaction of PT Sentra Bumi Nirwana employees, motivation has a significant positive effect directly on job satisfaction of PT Sentra Bumi Nirwana employees, and incentives, discipline, and motivation have a significant positive effect together on the job satisfaction of PT Sentra Bumi Nirwana employees.